Desain Perkuliahan Pengembangan Materi Ajar untuk SD dengan LMS Google Classroom di Masa Pandemic COVID-19 - Dede Trie Kurniawan; Sri Maryanti; Nailah Tresnawati (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This research is constituted by the phenomenon of Covid-19 that changes the process of learning in universities in Indonesia. Thus, many lectures should develop models of online teaching. This study aims to expand lecturing models in networks through utilizing digital Information Comunication Technology for prospective elementary school teacher. This study attempts to produce methods and designs of digital classroom lectures particularly for thriving teaching materials in elementary schools and escalating metacognition at faculty of education, University of Swadaya Gunung Djati, Cirebon, Jawa Barat. The research method used Development Research with the ADDIE model which is directed to flourish lecture methods in networks for prospective elementary school teacher in exerting digital Information Comunication Technology. This research tries to expand methods and design digital classroom lectures in evolving elementary teaching materials with the Google Classroom Learning Management System and improving their metacognition.